芝麻酱对双侧卵巢切除所致大鼠骨质疏松症的影响Effect of sesame paste on osteoporosis of rats induced by bilateral ovariectomy - 邱敏1,2，王惠敏1,2，鹿杰1，赵雷振1,2，任长博3，袁文鹏1,2 QIU Min1,2,WANG Huimin1,2,LU Jie1,ZHAO Leizhen1,2, REN Changbo3,YUAN Wenpeng1,2 (Zhongguo youzhi, 2022)
为了解芝麻酱是否有补钙效果，研究了芝麻酱对双侧卵巢切除雌性SD大鼠所致骨质疏松症的影响。选取健康雌性SD大鼠作为研究对象，除假手术组外，其余均采用切除双侧卵巢的方法建立雌性大鼠骨质疏松模型。造模成功后，将卵巢切除大鼠随机分为模型组，葡萄糖酸钙组〔0.56 g/(kg·d)〕，芝麻酱低〔1.04 g/(kg·d)〕、中〔2.08 g/(kg·d)〕、高剂量组〔4.16 g/(kg·d)〕，分别灌胃生理盐水、葡萄糖酸钙、芝麻酱12周后，检测芝麻酱对大鼠体质量、脏器系数、血清生化指标、骨强度、骨钙含量、骨组织形态学等的影响。结果表明：切除卵巢12周后，与假手术组相比，切除双侧卵巢的大鼠体质量极显著增加（p＜0.01），子宫形态明显萎缩，骨质疏松情况明显加重，提示造模成功。连续灌胃芝麻酱12周后，与模型组比较，芝麻酱各剂量组大鼠的体质量、脏器系数、骨强度、骨钙含量及骨组织结构无显著变化；芝麻酱低、中剂量组大鼠血清磷的水平极显著升高（p＜0.01），血清碱性磷酸酶的水平显著降低（p＜0.05），芝麻酱中剂量组大鼠血清钙的水平极显著升高（p＜0.01），芝麻酱高剂量组大鼠血清磷的水平显著升高（p＜0.05）；芝麻酱各剂量组大鼠血清总胆固醇、甘油三酯、高密度脂蛋白胆固醇无显著变化。因此，芝麻酱可在一定程度上改善双侧卵巢切除大鼠与骨代谢相关的血液指标，但对骨骼系统的影响不显著。 In order to understand whether sesame paste had calcium supplement effect, the effect of sesame paste on osteoporosis of female rats induced by bilateral ovariectomy was investigated. Healthy female SD rats were selected as the research objects, except for the sham operation group, the rest rats were all removed the bilateral ovaries to establish a female rat osteoporosis model. After successful modeling, the ovariectomized rats were randomly divided into model group, calcium gluconate group〔0.56 g/(kg·d)〕, and the low〔1.04 g/(kg·d)〕, middle〔2.08 g/(kg·d)〕 and high〔4.16 g/(kg·d)〕doses groups of sesame paste. After 12 weeks of intragastric administration of normal saline, calcium gluconate, and sesame paste, the effects of sesame paste on the body weight, organ coefficient, serum biochemical indicators, bonestrength, bone calcium content, and bone tissue morphology of rats were tested. The results showed that after the removal of the ovaries for 12 weeks, compared with the sham operation group, the body weight of ovariectomized rats was significiently increased (p＜0.01), the uterine shape was significantly atrophy, and the osteoporosis was significantly increased, indicating that the model was successfully constructed. After 12 weeks of continuous administration of sesame paste, compared with the model group, sesame paste did not significantly affect the body weight, organ coefficient, bone strength, bone calcium content and bone tissue structure of bilateral ovariectomized rats, low and middle dose of sesame paste could significantly increase the level of serum phosphorus of rats (p＜0.01) and significantly reduce the level of serum alkaline phosphatase of rats(p＜0.05), the middle dose of sesame paste could significantly increase the serum calcium level of rats (p＜0.01), and the high dose of sesame paste could significantly increase the serum phophorus level (p＜0.05), while sesame paste had no significant effects on serum total cholesterol, triglycerides, and high-density lipoprotein cholesterol. Therefore, sesame paste could improve the blood indicators related to bone metabolism in bilateral ovariectomized rats to a certain extent, but its effect on the skeletal system was not significant.